Novel diagnostic approaches for Fanconi anemia (FA) by single-cell sequencing and capillary nano-immunoassay. Issue 1 (January 2021) - Chang, Lixian; Gao, Xingjie; Ji, Guangzhen; Cheng, Xuelian; Zou, Yao; Cheng, Tao; Yuan, Weiping; Zhu, Xiaofan
Abstract : Abstract: Next-generation sequencing technology has been widely utilized for the diagnosis of Fanconi anemia (FA). However, mixed cell sequencing and chimerism of FA patients may lead to unconfirmed genetic subtypes. Herein, we introduced two novel diagnostic methods, including single-cell sequencing and capillary nano-immunoassay. One FA case with FANCM c.4931G>A p.R1644Q and FANCD1 c.6325G>A p.V2109I was studied. The DNA of 28 cells was amplified and eight types of cells were observed after Sanger sequencing. There were two homozygous mutations ( FANCM / FANCD1 ). Furthermore, the capillary nano-immunoassay was conducted to analyze the expression profile of FA-associated proteins. Abnormal FANCM and FANCD1 expressions simultaneously existed. This case was thus diagnosed as FA-D1/FA-M dual subtype. Compared with mixed cell sequencing, single-cell sequencing data shows more accuracy for the FA subtype evaluation, while the capillary nano-immunoassay is a good method to detect the expression profile of abnormal or modified FA protein.